The Eurosystem and the Single Supervisory Mechanism: Institutional continuity under constitutional constraints - Jakub Gren (European Central Bank (ECB), 2018)
This paper analyses regulatory solutions that have been adopted to address constitutional constraints imposed on the functioning of the Single Supervisory Mechanism (SSM), in which the ECB's exclusive supervisory competence is carried out. It argues that the operational framework governing the functioning of the SSM has assimilated, to a certain extent, three specific regulatory solutions underpinning the workings of the ESCB/Eurosystem: 1) the (legislative) allocation of certain tasks and responsibilities between ECB internal administrative bodies and structures; 2) the possibility of internal delegation of decision-making powers; and 3) the decentralised exercise of certain of the Union's tasks. Such a design of the SSM reflects institutional continuity concerning a political choice on how to achieve stage one of a genuine Economic and Monetary Union. It concludes that the Union operates at its best when centralised decision-making on substantial policy issues is combined with a decentralised operational framework allowing for the meaningful involvement of national administrations in the exercise of Union exclusive competences.
Keywords: K10; K40; 330; ECB; Eurosystem; SSM; decentralisation; delegation